(untitled) (Annals of Medical Research, 2023)
Aim: The PAIR (Puncture, Aspiration, Injection of scolicidal agent, and Reaspiration) treatment is used for echinococcosis type 1 (CE1) liver hydatid cysts. The aim of this study is to show the relationship between the cyst diameter and long-term results of PAIR. Materials and Methods: Between 2016 and 2021, fifthy patients with 54 liver CE1 hydatid cysts who underwent PAIR treatment were included in the study. Under general anesthesia, procedures were carried out. Technical success (completing the required steps in a procedure), clinical success (absence of recurrence or major complication upon follow-up), complications, cyst cavities’ long-term alterations were evaluated. Inactivation times of cysts smaller than 6 cm and larger than 6 cm were compared. Results: The long axis of the cysts was between 3 cm and 12 cm. Technical success rate was 100%. The average follow-up time was 996 ± 250 days. The cysts showed a mean volume reduction of 70.1% on follow up. The treatment was effective in 48 patients and 52 hydatid cysts. The effectiveness of the long-term treatment was 96%. Cysts smaller than 6 cm had a significantly shorter inactivation time than cysts larger than 6 cm (p=0.01). Recurrence (CE2) was detected in one patient (2 %). This patient was treated with the modified catheterization (MoCAT) technique. Major complication (abscess) was detected in one patient (2 %) and abscess was drained using the percutaneous seldinger technique. Intra-abdominal spread, anaphylaxis, or mortality did not develop in any patient. Post-procedural pain developed in 3 patients as a minor complication (6 %). Conclusion: Although the inactivation time is longer in cysts larger than 6 cm, PAIR technique used to treat liver CE 1 hydatid cysts are effective and secure.